(X, T)-phase diagram of TlIn(S1–xSex)2 solid solutions (x = 0, 0.02, 0.06, 0.10, 0.15 and 0.25). Temperature dependences of thermal expansion and optical anisotropy parameters. (1st September 2020) - Adamenko, Dmitro; Say, Andriy; Martynyuk-Lototska, Irina; Mys, Oksana; Kostyrko, Myroslav; Gommonnai, Oleksandr O.; Gomonnai, Aleksandr V.; Vlokh, Rostyslav
ABSTRACT: Basing on dilatometric and optical anisotropy studies, we have obtained (x, T)-phase diagram for TlIn(S1–x Sex )2 solid solutions in the range 0 ≤ × ≤  0.25 of selenium concentrations. It has been found that increasing selenium concentration leads to decrease in almost all of phase transition (PT) temperatures. At the same time, the temperature Ti of PT into incommensurate phase for the polytype c  =  c 0 increases at the selenium concentrations higher than 0.1, and we observe a tendency to broadening of the temperature region where the incommensurate phase exists. The incommensurate–ferroelectric PT reveals a notably diffuse character. We have also demonstrated that the TlIn(S1–x Sex )2 solid solutions have a polytype structure. It manifests itself in availability of additional PT in the solid solutions with 0 ≤ × ≤  0.05. Most probably, the latter corresponds to ferroelectric transformation in the polytype with c  = 16 c 0 .